Air Starting System Reliability Uses Reliability Requirement Setting (RRS) Model and Management Action Selection (MAS) Method - Bhimadi, Tungga (oneamd.com, 2024)
Interpretation of the reliability can be used as a quality measurement of operational system of safety. We propose maintenance methodology based on reliability as a solution for predicting reliability system. To make a convenience system appropriate with regulation, we begin to define the three reliability scopes, they are: interval reliability, component reliability, and system reliability. Proposal of Engineering Calculation is the RRS Model for predicting design of component reliability and MAS Method to correct reliability caused by real operation. MAS method consists of harmonization of maintenance schedule, resetting or hazard or overhaul, revitalization (component reliability improvement), and innovation (component replacement with actual part). Case study to implement these model and method based on Air Starting System of Tanker. Predict of system reliability design is 0.438044295. To obtain reliability based on regulation, it is necessary to do overhaul once in every five years. Innovation and revitalization for valve follow procedure of MAS method also done in every five years